Transition into the sexual and reproductive role: a qualitative exploration of Iranian married adolescent girls’ needs and experiences - Kohan, Shahnaz (Reprod Health, 2021)
BACKGROUND: It is necessary to invest in married adolescent girls’ health because of their roles in promoting the community and health of the next generation. Meanwhile, there are many concerns about their sexual and reproductive health. The International Conference on Population and Development emphasized the importance of access to adolescent girls to reproductive health services and counseling. In Iran, about 24% of registered marriages are to girls under 19, while their sexual and reproductive health needs have neglected. Therefore, this study aimed to identify married adolescent girls’ reproductive and sexual needs. METHODS/DESIGN: Data were obtained through in-depth, semi-structured individual interviews with 36 participants, including 11 women who got married at 10 to 21 years of age, two mothers whose daughters were married in adolescence, and 23 healthcare providers and policymakers. The participants were selected through purposive sampling with maximum variation. Data collection continued until data saturation. The interviews were analyzed by qualitative content analysis. Similar codes were merged, and sub-categorization was performed, whereby similar categories were combined until the main categories that emerged. RESULTS: The results revealed five main categories: preparing for marriage, enhancing awareness and decision—making power on sexual and reproductive health issues, developing adolescent-friendly sexual and reproductive services, providing tailored pregnancy and childbirth services, and preparing adolescents for motherhood. CONCLUSION: Adolescents step into marital life without the required life skills or physical and mental preparedness. They often become pregnant due to social pressures and lack of access to contraception. Therefore, in countries like Iran, where there is a high frequency of early marriage, families, education, and the health system should prepare the necessary foundation to support these adolescents and provide tailored and comprehensive sexual and reproductive health services.